Quantitative Muscle MRI and Clinical Findings in Women With Pathogenic Dystrophin Gene Variants - Fornander, Freja; Solheim, Tuva Åsatun; Eisum, Anne-Sofie Vibæk; Poulsen, Nanna Scharff; Andersen, Annarita Ghosh; Dahlqvist, Julia Rebecka; Dunø, Morten; Vissing, John (Frontiers in Neurology, 2021)
Objective: To explore fat replacement, muscle strength, and clinical features in women heterozygous for a pathogenic DMD variant, we prospectively examined 53 women, assuming that some of these women—despite of the recessive X-linked inheritance—manifested clinical symptoms. Methods: We performed a cross-sectional observational study using MRI and stationary dynamometry of lower extremities, extracted blood muscle biomarkers, and investigated subjective complaints. Results were compared with 19 healthy women. Results:DMD variant carriers were weaker and had higher fat fractions than controls in all investigated muscle groups (p < 0.02). Fat fractions were 18% in carriers vs. 11% in controls in thighs (p = 0.008), and 15 vs. 11% in calf muscles (p = 0.032). Seventy-two percent had fat fractions deviating from controls by two standard deviations (SDs) in one or more of the 16 investigated muscle groups. On strength testing, 40% of the carriers had results deviating from control muscle strength by two SDs in one or more dynamometry assessments. Forty-three carriers (81%) had either reduced muscle strength (<2 SDs from control mean) and/or elevated muscle fat fraction (>2 SDs from control mean). Thirty of these had subjective symptoms. Blood creatine kinase and myoglobin were elevated in 57% of the carriers. Conclusion: Using quantitative methods, this study shows that both clinically symptomatic and asymptomatic women with pathogenic DMD variants show a high prevalence of muscle affection. Longitudinal studies in female carriers of pathogenic DMD variants are needed to follow the evolution of these changes.